2014
DOI: 10.7318/kjfc/2014.29.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Rheological Characteristics of the Mixed Wheat Flour Containing Bamboo and Lotus Leaf Powder

Abstract: The purpose of this study was to investigate the rheological characteristics of medium wheat flour mixed with bamboo leaf and lotus leaf powders. Rheological properties of the mixed flours were tested based on falling number, color, RVA, farinogram, and rheofermentometer analyses. Falling numbers increased with addition of bamboo leaf and lotus leaf powders. The L values of all mixed flours were less than that of control. The 1% mixed flour sample containing bamboo leaf and lotus leaf powders was not significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For mixed flours, the rheology studied by Hwang et al (2014) reportedly found increase in falling number of wheat flour by adding lotus leaf powder and bamboo leaf powder ranging from 1 to 3% which reduced the pasting properties, that is peak viscosity, final viscosity and holding strength; however, the setback values of mixed wheat flour added with bamboo leaf powder were lower than those of mixed wheat flour added with lotus leaf powder, thereby concluding that bamboo leaf powder suppressed retrogradation of flour compared to lotus leaf powder.…”
Section: Lotus Starch and Its Characteristicsmentioning
confidence: 99%
“…For mixed flours, the rheology studied by Hwang et al (2014) reportedly found increase in falling number of wheat flour by adding lotus leaf powder and bamboo leaf powder ranging from 1 to 3% which reduced the pasting properties, that is peak viscosity, final viscosity and holding strength; however, the setback values of mixed wheat flour added with bamboo leaf powder were lower than those of mixed wheat flour added with lotus leaf powder, thereby concluding that bamboo leaf powder suppressed retrogradation of flour compared to lotus leaf powder.…”
Section: Lotus Starch and Its Characteristicsmentioning
confidence: 99%